2015
DOI: 10.1002/brb3.414
|View full text |Cite
|
Sign up to set email alerts
|

Induction of neural differentiation in rat C6 glioma cells with taxol

Abstract: BackgroundGlioblastoma is a common and aggressive type of primary brain tumor. Several anticancer drugs affect GBM (glioblastoma multiforme) cells on cell growth and morphology. Taxol is one of the widely used antineoplastic drugs against many types of solid tumors, such as breast, ovarian, and prostate cancers. However, the effect of taxol on GBM cells remains unclear and requires further investigation.MethodsSurvival rate of C6 glioma cells under different taxol concentrations was quantified. To clarify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 37 publications
4
8
0
Order By: Relevance
“…It can be seen that GFAP was abundantly expressed in the normal brain tissue zone but was barely expressed in the glioma zone. This was consistent with the previous findings, which demonstrated that C6 cells remain in an undifferentiated state and cannot be recognized by GFAP [43]. Based on their histological traits and biological behaviour, C6 glioma cells have been reported to correspond to human anaplastic astrocytoma of grade II/III [44], indicating that QDs-c(RGDyk)NP might be used as a tracer of human glioma in the future.…”
Section: He and Immunohistochemistry Staining Of Gliomasupporting
confidence: 92%
“…It can be seen that GFAP was abundantly expressed in the normal brain tissue zone but was barely expressed in the glioma zone. This was consistent with the previous findings, which demonstrated that C6 cells remain in an undifferentiated state and cannot be recognized by GFAP [43]. Based on their histological traits and biological behaviour, C6 glioma cells have been reported to correspond to human anaplastic astrocytoma of grade II/III [44], indicating that QDs-c(RGDyk)NP might be used as a tracer of human glioma in the future.…”
Section: He and Immunohistochemistry Staining Of Gliomasupporting
confidence: 92%
“…Induced neural differentiation of paclitaxel-treated C6 glioma cells through cell morphologic changes with expression of neural markers was recently reported [33]. Extended morphology of αB-crystallin-overexpressing cells but not αB-crystallin knockdown cells was dramatically reduced by a microtubule stabilization agent, paclitaxel, indicating that stretched morphology is dependent on αB-crystallin-assisted microtubule dynamic instability (Fig 5).…”
Section: Resultssupporting
confidence: 51%
“…Hence it will be of interest to investigate if NA affects the activation of GSK-3β and/or Akt and, if so, how these effects are related to intracellular calcium levels. Another important question is whether NA could induce the differentiation of glioma stem cells, as reported recently for other anti-cancer drugs such as taxol64. Although we did not observe any apparent changes in the level of stemness marker Nestin or differentiation marker β-tubulin with immunostaining (Figs 1 and 6J,K), more quantitative methods such as real-time RT-PCR and Western blot are needed to determine if there are any relatively subtle effects of NA on glioma differentiation.…”
Section: Discussionmentioning
confidence: 94%